Citizen Views on Punishment: the Difference between Talking and Deciding - Maria Ines Bergoglio (Oñati Socio-Legal Series)
In 2004, the Province of Córdoba, Argentina implemented lay participation in criminal decisions by means of Law 9182. The law was passed within a context of national debate concerning efficient measures to fight against insecurity and crime. These debates were brought about by a social movement led by Juan Carlos Blumberg, which demanded harsher penalties and judicial reform as means to improve urban safety.